Evaluation of four high‐protein rice‐soy snack formulations - Man, Yaakob B. Che; Abdul Karim, Mohamad N.B.; Kun, Tan T. (1992)
Four different formulations of rice‐soy snack containing 4.5%, 9.0%, 13.5%, and 18.0% full‐fat soy flour (FFSF) were evaluated for their nutritional values and acceptance. Protein content increased from 9.54% to 15.44% and chemical scores of the snacks from 86 to 100 but there was no difference in Net Protein Utilization although values were higher in snacks than in either rice or FFSF alone. All formulations were well accepted but at the highest level of FFSF (18%) acceptability was significantly (P<0.01) reduced. Copyright © 1992, Wiley Blackwell. All rights reserved